(untitled) (Canadian Journal of Emergency Management, 2025)
As disasters, climate emergencies, public health crises, and security threats and conflicts increase in Canada, so do concerns about their inequitable impacts. Canada’s 2023 Chief Public Health Officer’s Report, Creating the Conditions for Resilient Communities: A Public Health Approach to Emergencies, highlighted the unequal impacts of emergencies in Canada and advocated for an improved public health and health promotion response. This article describes the Gendered Emergency Management Framework (GEM-F), developed as a practical tool to support emergency personnel, planners, and policy makers in integrating sex, gender, trauma and equity-informed considerations across the emergency management continuum, applicable to climate disasters, pandemics or conflict situations. The GEM-F is built on academic evidence, grey literature, and consultations with Canadian and Australian experts, and suggests the integration of sex and gender based analysis plus (SGBA+), and trauma-informed, equity-oriented, and gender transformative approaches into all phases of emergency management. The consistent application of the GEM-F in policy, practice and training could improve preparedness and post-event outcomes, along with overall gender and health equity.